Status of Medical Laboratory Science Faculty and Programs. - FREEMAN, VICKI; BROWN, KAREN; FENN, JOANN PARKER; FONG, KAREN; GENZEN, JONATHAN; GOODYEAR, NANCY; HOUSTON, MARY LUNZ; TAFF, TERRY; TANABE, PATRICIA (Clinical Laboratory Science)
A survey conducted on the status of medical laboratory science (MLS) education programs was conducted. Information on university and hospital program directors and faculty salaries, education level, certification, clinical and teaching experience, and responsibilities was collected. Additionally, the characteristics and operations of MLS programs in the university and hospital settings, including staff education requirements, open positions, certification patterns, programlength, clinical sites, and teaching strategies, were obtained. A total of 160 respondents answered the university survey, and 119 respondents answered the hospital survey. The results summarize the characteristics of educational programs and Individuals who work in hospital and university settings as well as issues related to demographics, education level, rank, certification, experience, responsibilities, and salaries. Overall, university programs' education requirements were higher (aminimum of a master's degree) for MLS faculty, and the faculty were more likely to have doctoral degrees or postdoctoral training. In general, university programs had more faculty than hospital programs, and the university faculty and program directors also had higher median salaries. The top 3 areas in which university program directors had difficulty securing clinical sites were microbiology, blood bank, and molecular diagnostics. The top challenges to obtaining clinical sites included staffing, competition with other MLS/medical laboratory technology (MLT) programs, and increase in workload and time. Some programs used simulated labs when a clinical rotation site was unavailable. Generalizations on the survey results are limited because of the varying number of respondents to the survey questions, large standard deviations, and wide ranges. The American Society for Clinical Pathology (ASCP) board of certification is in the process of updating and redesigning the MLS survey of programs and faculty to facilitate responses and plan on implementing the survey in 2020. In addition, a survey on the status of MLT programs and faculty is in development. Both the MLS and MLT surveys of programs and faculty will be administered on a biannual basis, similar to the ASCP wage and vacancy surveys, so that data can be collected and analyzed longitudinally.